2006
DOI: 10.1128/aem.00998-06
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Frozen Lactobacillus delbrueckii subsp. bulgaricus in Glycerol Suspensions: Freezing Kinetics and Storage Temperature Effects

Abstract: The interactions between freezing kinetics and subsequent storage temperatures and their effects on the biological activity of lactic acid bacteria have not been examined in studies to date. This paper investigates the effects of three freezing protocols and two storage temperatures on the viability and acidification activity of Lactobacillus delbrueckii subsp. bulgaricus CFL1 in the presence of glycerol. Samples were examined at ؊196°C and ؊20°C by freeze fracture and freeze substitution electron microscopy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 28 publications
4
38
0
Order By: Relevance
“…Table IV shows that survival of E. coli after 71 days at À808C (71%) was significantly greater than at À108C (30%). This observation corroborates those of Fonseca et al (2006) who reported that the viability of L. bulgaricus cells was greater when stored at À808C than at À208C. This effect may be caused by the occurrence of vitrification at À808C (Fonseca et al, 2006).…”
Section: The Frozen Statesupporting
confidence: 91%
See 1 more Smart Citation
“…Table IV shows that survival of E. coli after 71 days at À808C (71%) was significantly greater than at À108C (30%). This observation corroborates those of Fonseca et al (2006) who reported that the viability of L. bulgaricus cells was greater when stored at À808C than at À208C. This effect may be caused by the occurrence of vitrification at À808C (Fonseca et al, 2006).…”
Section: The Frozen Statesupporting
confidence: 91%
“…The response of E. coli cells would suggest that the greater viability of cells in frozen compared with supercooled conditions is associated with the higher concentration of glycerol within the unfrozen fraction. It has been shown that the viscosity of the residual unfrozen solution to which all cells are exposed during freezing in the presence of glycerol increases rapidly (Fonseca et al, 2006). Hence, diffusion is limited because of high viscosity.…”
Section: The Frozen Statementioning
confidence: 99%
“…It was found that increasing the methanol concentration or using the glycerol as a buffer was very effective for reducing cell membrane damage. Previous studies confirmed that both methanol and glycerol were effective cryoprotectants for L. bulgaricus and had the ability to enhance the cell viability against freezing damage (Carvalho et al, 2004;Fonseca et al, 2006). Especially, glycerol as a permeable compound could protect freeze-dried lactic acid bacteria through inhibiting excess dehydration, reducing salt toxicity, and preventing ice crystals formation (Huang et al, 2006).…”
Section: Discussionmentioning
confidence: 92%
“…~10 and 30,000 °C min -1 , respectively). Fonseca et al (2006) also reported that high cooling rates significantly improve survival rates for lactic acid bacteria. It is worth noting that although freeze-drying usually causes more damage to cells than cryopreservation, we observed a minor loss of viability using this first method (Table 2, Table 3).…”
Section: Discussionmentioning
confidence: 94%
“…Leslie et al (1995) showed how some carbohydrates protect membranes during the rehydration process, decreasing the rate of transition in membranes from gel to the liquid crystalline phase. Other agents as glycerol or DMSO reduce the eutectic point of water preventing the formation of ice crystals (Fonseca et al 2006). Therefore, it is critical to select the appropriate protective agent for improving the storage conditions for Azotobacter cells.…”
Section: Discussionmentioning
confidence: 99%